"New Technologies" as imaginary meanings - Cabrera, Daniel (2022)
This paper constitutes an analysis of the so called new information technologies and communication, based on the main documents drafted due to its appearance, but mainly on those daily-handled public concepts that they themselves have generated, identified as ‘imaginary meanings’ —in Castoriadis's sense—. The article begins discussing some of the particular meanings given to new technologies in relation to social temporality, and concludes suggesting a matrix of social imaginaries, from which these meanings seem to originate and function. In this epystemologycal exercise, manifold perspectives on which it is not deepen are left open, leaving space for further discussion.